2014
DOI: 10.1002/bbb.1487
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for small‐scale biorefinery for production of sugar and ethanol in the Netherlands

Abstract: Developments such as the Common Agricultural Policy reform, growth of the bio‐based economy, increasing energy prices, increasing sustainability demands, and expected growth of global sugar demand change the environment in which the sugar producing industry operates. In order to remain competitive and profit from this, the traditional large‐scale sugar producing industry can adapt. The aim of this study was to address sustainability and energy issues of the traditional sugar production process and to provide o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 46 publications
0
44
0
Order By: Relevance
“…Proposition 13 refers to transportation distances and locality to keep emissions and costs low, and to allow for stream integration across production chain stages. Much has been studied in this regard, including optimization approaches and design principles for determining transportation distances and scale and the consideration of peripheral pre‐processing facilities . For BJF production, similar approaches could be considered with target airport location and possible biomass production sites as input.…”
Section: Resultsmentioning
confidence: 99%
“…Proposition 13 refers to transportation distances and locality to keep emissions and costs low, and to allow for stream integration across production chain stages. Much has been studied in this regard, including optimization approaches and design principles for determining transportation distances and scale and the consideration of peripheral pre‐processing facilities . For BJF production, similar approaches could be considered with target airport location and possible biomass production sites as input.…”
Section: Resultsmentioning
confidence: 99%
“…However, significant energy input can especially affect small-and medium-sized enterprises with low degrees of heat integration. [32] In this regard, energy-demanding distillation of BDO can be implemented for the large-scale companies, but is less suitable for small-scale biorefineries. Because the method proposed herein for BDO recovery does not include any heating operations, it is expected to be energy efficient and appropriate for small-scale refineries.…”
Section: Conversion Of Bdo Into Mekmentioning
confidence: 99%
“…Bioethanol is an alternative biofuel or additive to gasoline and is also used as a chemical feedstock for bio-ethylene production. Commercial production of bioethanol has been performed using corn and sugarcane as a source of biomass, and it was recently reported that construction of demonstration facilities for lignocellulosic bioethanol was under way worldwide (Kolfschoten et al, 2014;Richard, 2010). Meanwhile, the yeast Saccharomyces cerevisiae is a GRAS microorganism and a robust bioethanol producer used for commercial processes (Kim et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%